O conceito de leitura nos PCN de língua portuguesa para o Ensino fundamental II: uma análise dialógica - Costa, Maíra Aparecida Reis (2020)
The present work was developed from documentary research and seeks to answer the question: "What is the conception of reading that underlies the National Curriculum Parameters to Portuguese Teaching"? We start from the hypothesis that the conception of reading that guides national documents, such as, for example, the National Curriculum Parameters to Portuguese Teaching, approaches and, at the same time, distances itself from a dialogical conception of reading, which is essential for the formation of the reader, so that he can understand what is implicitly or explicitly written, said, and felt. From the study of authors such as Mikhail Bakhtin, Paulo Freire, Luiz Carlos Cagliari, Ramón Flecha, Jürgen Habermas, Angela Kleiman, Ingedore Villaça Koch, Vanda Maria Elias, Vilson J. Leffa, Isabel Solé, among others. Intending to provide a discussion as to the conceptions of reading under the National Curriculum Parameters to Portuguese Teaching, a guiding document of teaching practice at national level for the final years of Elementary Education, the reason for its realization is the need to discuss Reading processes and coach readers in the final years of elementary school, given that the reading experience, regardless of the genre, must have a meaning for the student, and the fact that the school is one of the main - if not the main - spaces where reading takes place. We analyze the conception of reading in the National Curriculum Parameters to Portuguese Teaching, using the cognitive reference of reading and the dialogical reference of reading. We identified that the National Curriculum Parameters to Portuguese Teaching by valuing the reader's previous knowledge, the situations of communication and interaction helps readers to learn to read more effectively. We realize that there are many positive aspects in the National Curriculum Parameters to Portuguese Teaching, as it suggests readings to be carried out by teachers, projects, suggesting an infinity of textual genres and make the act of teaching more flexible. Such opening, however, has a two-way street: reading and mechanical practices can be performed, depending on the conditions of the school and the training of teachers. In this sense, we identified that the training of readers and reading practices in the classroom involve aspects much more complex than the situations faced by teachers in the classroom. Therefore, we conclude that it is necessary to invest in undergraduate courses, in continuing teacher training, in school infrastructure and in local libraries. Training readers involves the environment, the community, not just the school. The referential of dialogical learning is very close to the concepts proposed by the National Curriculum Parameters to Portuguese Teaching, which confirms our hypothesis. The dialogical reference, guide of this work, has also contributed to the discovery of elements that help answer that reading has several aspects, contributing to learning, communication, enjoyment and, especially, to read the word and read the world we are in. The National Curriculum Parameters to Portuguese Teaching for the final years of elementary education, in this sense, approach and depart from the assumptions of this framework.